The association between aggression, traumatic event exposure and post-traumatic stress disorder of looked after young people - Rachel Eleanor Webb; Dan Johnson (Scottish Journal of Residential Child Care, 2019)
This study identified an association between symptoms of post-traumatic stress disorder (PTSD) and aggression in a sample of looked after young people. Observational data on PTSD symptoms and the frequency of aggressive behaviours was obtained for a sample of 36 boys and 13 girls in residential and secure care over a retrospective 28 day period. The study identified high rates of traumatic event exposure and PTSD symptoms, with 51% meeting the criteria for a likely diagnosis of PTSD. The severity of PTSD symptoms was also found to be associated with verbal and physical aggression towards members of staff and peers within the care environment.